Efektivitas Pelatihan Positioning Branding Dalam Meningkatkan Brand Equity Bagi Pelaku UMKM Kelurahan Tenggilis Mejoyo Kota Surabaya - Silvia Rahmawati; Sugito Sugito (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted through branding positioning training activities to strengthen MSME brand equity in Tenggilis Mejoyo Village, Surabaya City. The results of surveys and interviews show that MSME players face problems in branding and lack of utilisation of digital technology. Through training, MSME players are given an understanding of the importance of branding, the use of social media, e-commerce, logo making, and packaging. The evaluation showed that the training was effective in increasing knowledge and understanding of branding, potentially strengthening brand equity, and providing strategies for MSMEs to compete in the digital era. In conclusion, branding positioning training plays an important role in developing MSMEs and increasing marketing success.